2021
DOI: 10.1186/s40538-020-00203-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of subcritical water extraction of phenolic compounds from Ziziphus jujuba using response surface methodology: evaluation of thermal stability and antioxidant activity

Abstract: Background The jujube is mainly grown in the subtropical and tropical regions of Asia. Due to owning bioactive compounds such as polyphenols, it was considered as medicinal and nutritional plant in traditional medicine. This study aimed to extract phenolic compounds from Ziziphus jujuba using subcritical water (SCW) process. The possible combinations of temperature, time, and fruit-to-solvent ratio were investigated using response surface methodology. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The predominant peak in the UV-Vis spectra of all the water-soluble products was observed at approximately 280 nm. We hypothesized that the intramolecular hydrogen bonds of the phenolic groups of the lignin component of the apple peel were destroyed during subcritical water treatment [23][24][25]. Ersan et al [23] extracted the components of Pistacia vera L. hull, including phenolic compounds, using subcritical water in the temperature range of 110-190 °C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The predominant peak in the UV-Vis spectra of all the water-soluble products was observed at approximately 280 nm. We hypothesized that the intramolecular hydrogen bonds of the phenolic groups of the lignin component of the apple peel were destroyed during subcritical water treatment [23][24][25]. Ersan et al [23] extracted the components of Pistacia vera L. hull, including phenolic compounds, using subcritical water in the temperature range of 110-190 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Lachos-Perez et al [24] also used subcritical water to extract phenolic compounds from defatted orange peel in the temperature range of 110-150 °C. Furthermore, Niazmand et al [25] optimized the extraction of phenolic substances from Ziziphus jujuba using the subcritical water technique. Using a response surface method, they evaluated the effect of temperature on the extraction process and confirmed that the extraction yield of phenolic substances increased significantly upon increasing the temperature from 110 to 170 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subcritical water extraction (SWE) is an alternative green method for eliminating the use of toxic organic solvents for the extraction of bioactive compounds. In SEW, subcritical water is maintained at high temperature and pressure to retain the liquidity of subcritical water (critical temperature of water = 374 °C, critical pressure of water = 22.1 mPa) (Niazmand et al ., 2021). At high temperatures, water has a lower dielectric constant, which reduces the strength of the hydrogen bonds and reduces its polarity reaching a polarity level similar to that of methanol and ethanol, thus making it capable of extracting a wider range of phenolic compounds (Ko et al ., 2020).…”
Section: Subcritical Water Extractionmentioning
confidence: 99%